PENGARUH WORK LIFE BALANCE DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT YAMAHA MUSIC MANUFACTURING INDONESIA (Studi Kasus Departemen Produksi) - Mardiyana, Mardiyana; Hidayat, Rahmat (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to determine the effect of Work Life Balance, Non-physical Work Environment, and Job Satisfaction on Employee Performance at PT Yamaha Music Manufacturing Indonesia, especially in the production department of research methods using quantitative approaches. The population used in this study was employees of PT Yamaha Music Manufacturing Indonesia in the production department as many as 133 samples. The data used in this study are primary and secondary data, namely by distributing questionnaires and through google forms to employees of PT Yamaha Music Manufacturing Indonesia. The analysis technique in this study used the Lisrel 8.8 application. The results of this study are (1) Work Life Balance does not affect job satisfaction, (2) Non-physical Work Environment affects Job Satisfaction, (3) Work Life Balance and Nonphysical Work Environment simultaneously affect Job Satisfaction, (4) Work Life Balance does not affect Employee Performance, (5) Non-physical Work Environment affects Employee Performance, (6) Job Satisfaction affects Employee Performance, and (7) Work Life Balance, Non-physical Work Environment and Job Satisfaction simultaneously have no effect on Employee Performance.